PENERAPAN METODE HUNGARIAN DAN APLIKASI QM UNTUK MEMINIMALISASI KOMPLAIN KEBERSIHAN DARI KLIEN - Epin Nur Cahya; Nina valentika; Isnurani; Siti Hadijah Hasanah (Jurnal Matematika Sains dan Teknologi, 2022)
An outsourcing company with a work contract period can run well if the work agreement made by the client is carried out properly. One of the things that affect the contract period is client complaints. By minimizing client complaints, the sustainability of work contracts between outsourcing companies and client companies is getting higher. For this reason, outsourcing companies assign workers based on the abilities of each worker so that the work results are optimal. One of the methods in solving assignment problems is the Hungarian method and the QM application. The purpose of this research is to minimize the value of hygiene complaints from clients. The results showed a reduction in the value of 15 client complaints from 43 complaints to 28 complaints related to the completion of the assignment of employees of outsourcing company using the Hungarian method and the QM application.